Kebijakan Spasial dalam Pemetaan Persebaran Covid-19 Di Kota Surabaya - Indah Novita Sari; Agus Wahyudi (Public Sphere Review, 2022)
This study aims to describe and analyze the spatial policy of mapping the spread of Covid-19 in the Surabaya City Government. This research focuses on the policy environment, policy actors and public policy. The type of research used in this research is descriptive qualitative research with a case study approach. Data collection techniques used are observation, interviews, and documentation. The results of the study conclude that spatial policy is a policy issued or approved by the government related to the spatial or spatial distribution of the Covid-19 in the City of Surabaya. This mapping is also felt by the implementing parties to make it easier to provide quick and responsive handling, and can make it easier for the community to receive information and also increase their awareness in their activities. Spatial policies in mapping the spread of Covid-19 in the city of Surabaya are influenced by the policy environment, policy actors, and public policy itself. However, of the three variables, there is one variable that is still not going well, namely the policy environment variable. This is because the high number of Covid-19 cases in Mojo Village is caused by people's behaviors who do not comply with health protocols and underestimate the dangers of Covid-19. So that the role of the Surabaya City Government is needed in providing education and socialization to the public about covid 19